The current and future status of rare earth permanent magnets. (September 2018) - Nakamura, Hajime
Abstract: With their excellent magnetic performance, Nd-Fe-B magnets have a large share of the permanent magnet market, even after the sudden rise in the price of rare earths in 2011, which have been supported by magnet manufacturers' efforts to save heavy rare earths. The demand for high performance magnets is expected to increase, and both magnet users and manufacturers therefore welcome alternative magnets containing less or no rare earths. A knowledge of thermodynamics and understanding of the mechanism of coercivity of Nd-Fe-B may become very useful to develop processes for new magnets. Furthermore, cost-performance must never be neglected in practical use. Graphical abstract: Image 1